Determinants of Employee Performance with Work Motivation as an Intervening Variable at the Semarang City Search and Rescue Office - Setyowati, Widhy; Sofingi, Aris; Setyowati, Widhi (Pandawan, 2022)
Employees are the main key in increasing productivity and the success of agency activities. Employees have an important role in reducing or minimizing the impact of loss or damage caused by a disaster. This study aims to analyse and empirically test the influence of leadership on employee work motivation, organizational culture on employee work motivation, leadership on employee performance, organizational culture on employee performance, work motivation on employee performance, work motivation in mediating the influence of leadership on employees. performance, and work motivation in mediating the influence of organizational culture on employee performance. The method in this study using the sampling method, the population in this study is the SAR Department of Semarang City. The research sample was 125 samples. The results show that leadership has a positive effect on work motivation, organizational culture has a positive effect on work motivation, leadership has a positive effect on performance, organizational culture has a positive effect on performance, work motivation has a positive effect on performance, leadership has a positive effect on performance through work motivation, and culture organization has a positive effect on performance through work motivation. The conclusion from the results of this study is that the leadership that has been carried out has a positive impact on employees at the Semarang City Search and Rescue Service